1998
DOI: 10.1002/(sici)1099-0682(199812)1998:12<1967::aid-ejic1967>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Some Silatetraazaspiroalkanes with [4 + 4] Octacoordinated Silicon

Abstract: Spirocyclic compounds containing an Si(N)4 core have been prepared from 1,2‐ethane‐ and 1,3 propanediamines bearing the electron‐withdrawing p‐toluenesulfonyl groups at the four N atoms. According to the X‐ray structure analysis of the compounds 8a and 13, the spirocyclic rings are almost perpendicular to each other. In both cases a distorted dodecahedral arrangement of a [4 + 4] octacoordinate Si atom is found in which one O atom of each of the four sulfonyl groups caps one of the planes defined by the Si(N)4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…42 Comparable Si-O and Si-N distances were found by Rong and Wollenweber et al who discussed comparable structures with tosyl groups as substituents at the nitrogen atoms in terms of a [4 + 4] octacoordination with a tetrahedral SiN 4 core and four oxygen atoms in the "outer sphere", capping the tetrahedral planes. [43][44][45] The chemical shifts of the 29 Si NMR signals of monomer 1 in the solid state and the solution state are similar which indicates the same bonding motif (Fig. S3 in the ESI †).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…42 Comparable Si-O and Si-N distances were found by Rong and Wollenweber et al who discussed comparable structures with tosyl groups as substituents at the nitrogen atoms in terms of a [4 + 4] octacoordination with a tetrahedral SiN 4 core and four oxygen atoms in the "outer sphere", capping the tetrahedral planes. [43][44][45] The chemical shifts of the 29 Si NMR signals of monomer 1 in the solid state and the solution state are similar which indicates the same bonding motif (Fig. S3 in the ESI †).…”
Section: Resultsmentioning
confidence: 85%
“…For bond lengths and angles, as well as data acquisition details see ESI † (Table S2, octacoordination with a tetrahedral SiN 4 core and four oxygen atoms in the "outer sphere", capping the tetrahedral planes. [43][44][45] The chemical shift of the 29 Si NMR signals of monomer 1 in solid state and solution state are similar which indicates the same bonding motif (Fig. S3 in ESI †).…”
Section: Synthesis Of Hybrid Materialsmentioning
confidence: 74%
“…Recently, sulfonamides have also been used in the organic synthesis reactions for the synthesis of linear or cyclic oligomers and the introduction of nucleophilic heteroatom functionality to the synthesized molecule (Ni et al, 2015). N,N 0 -ditosylalkane diamine is a disulfonamide synthesized by the tosylation of diamine, and this synthetic molecule has antibacterial properties (Alyar et al, 2011) and has also been used in many organic synthesis reactions (Rong et al, 1998). In this study, the synthesis, crystal structure and Hirshfeld surface analysis are reported for the new potential sulfa drug, N,N 0 -[ethane-1,2-diylbis(oxy)]bis(4methylbenzenesulfonamide).…”
Section: Chemical Contextmentioning
confidence: 99%
“…In Abbildung 1 ist die röntgenographisch bestimmte tetracyclische Struktur von 5 gezeigt. [11] Bei [12] muû die Verdrillung auf die Alkylenbrücken zwischen den Spiroeinheiten zurückzuführen sein. Drei der vier Stickstoffatome sind pyramidal umgeben, was bei zwei Diazasilacyclopentenringen zu Pseudo-Briefumschlag-Konformationen führt.…”
unclassified
“…Ausgewählte Bindungslängen [] sowie Bindungs-und Torsionswinkel[8]: N-Si 1.7132(15) ± 1.7182(13); N1-Si-N16 91.81(7), N1-Si-N7 115.46(7), N1-Si-N10 121.96(7), N7-Si-N10 92.08(7); N16-Si-N1-C2 179.68(15), N16-Si-N1-C18 7.26(11), N1-Si-N16-C15 À 171.47(13), N1-Si-N16-C17 À 6.97, N10-Si-N7-C6 À 173.26(14), N10-Si-N7-C8 À 5.92(12), N7-Si-N10-C11 À 175.09(15), N7-Si-N10-C9 5.92(12).…”
unclassified